(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Healthcare workers in healthcare facilities may be exposed to a variety of work-related hazards, putting them at risk for numerous occupational injuries and diseases. Accordingly, the purpose of this study is to determine the occupational risks faced by healthcare personnel in government hospitals in the province of Duhok, Iraqi Kurdistan Region. This study was conducted among 400 healthcare professionals (152 physicians and 248 nurses). The previous 12 months' prevalence of risky events was; work overload 344 (86%), followed by stress during working 334 (83.5%). 312 (78%) had direct contact with body fluids of patients, The prevalence of needle stick injuries was 274 (68.5 %), 246 (61.5 %) of them had lifted heavy objects, either equipment or patients, cuts with sharp was 206 (51.50%), assault behaviour from relatives of the patient was 97 (24.25 %), 140 (35 %) of HCWs had either trips, slips and falls at the workplace, and at the same time, the lowest two risks were spills of chemicals material and assaults behaviour from patients, 95 (23.75%) and 69 (17.25%), respectively.